The Impact Of Liquidity And Profitability On Firm Value With Dividend Policy As An Intervening Variable (Empirical Study Of Manufacturing Companies In The Pharmaceutical Sub Sector Listed On The Indonesia Stock Exchange In 2013-2017) - Dian Kristianti; John E. H. J. Foeh (Jurnal Bisnis dan Kewirausahaan, 2020)
The purpose of this research is to know the description of corporate value and the influence of liquidity and profitability to firm value with dividend policy as intervening variable of pharmaceutical sub sector manufacturing companies listed in Indonesian Stock Exchange from 2013 until 2017. Liquidity in this research is measured by using current ratio (CR), profitability is measured by return on equity (ROE), dividend payout ratio (DPR), and firm value measured by price to book value (PBV). This research uses secondary data obtained from pharmaceutical sub-sector manufacturing companies listed in Indonesia Stock Exchange. Data analysis method uses Quantitative Descriptive Analysis, Multiple Linear Regression Analysis and Path Analysis. Data is processed using SPSS data analysis package software version 24.0. The overall conclusion is liquidity and profitability simultaneously or partially have a positive and significant effect on dividend policy, while liquidity, profitability, and dividend policy simultaneously have a positive and significant effect to firm value. But partially liquidity and profitability have a negative and significant effect to firm value, while dividend policy has a positive and significant effect to firm value. And, dividend policy is able to mediate the influence of liquidity and profitability to the value of pharmaceutical sub-sector manufacturing companies listed in Indonesia Stock Exchange.